Macroeconomic Determination of Indonesian Bank Interest Rates - Itto Turyandi; Mohd Kasturi Nor Abd Aziz; Ermi Triaji; Muhammad Al Mighwar; Usep Deden Suherman (Journal of Islamic Economics and Business, 2024)
The determination of interest rates by Bank Indonesia plays an important role in supporting national economic stability and growth. Although previous studies have highlighted the relationship between interest rates and economic growth and market performance, studies on macroeconomic determinants of interest rate determination are still limited. This study aims to analyze the effect of inflation and exchange rates on Bank Indonesia's interest rates in the period 2004 to 2023, covering both crisis and non-crisis periods. The method used is a quantitative approach with multiple linear regression analysis, as well as classical assumption tests to ensure the validity of the model. The results of the study show that inflation has a positive and significant effect on interest rates, while the exchange rate does not show a significant effect. This finding indicates that inflation is the main factor that Bank Indonesia considers in determining interest rate policy. The policy implications of this study emphasize the importance of controlling inflation in order to maintain the effectiveness of monetary policy and long-term economic stability.